The Tension Between Chinese Peasants’ Family Capital Reproduction Strategies and Massification in Higher Education - Dong, Jingyi (International Journal about Parents in Education, 2023)
This paper is focused on the tension between Chinese peasants' family capital reproduction strategies and the existing higher education system. Under an institutionalised urban-rural segregation, most rural residents are not entitled to some of the basic social welfare guarantees available to urban residents, such as pensions. As a preparation for the future of their children as well as for themselves, peasants have a strong urge to invest in their children's higher education as their family capital reproduction strategy. However, higher education institutions, without sufficient funding from the government, have to increase enrolment size and charge high tuition fees. Increase in the cost of higher education has strongly impacted on the family economy of rural residents, and the rapid expansion of the system has resulted in an employment crisis for college graduates. Bourdieu's theory of capital reproduction will be applied in the analysis of several cases of rural parents and their children who have participated in higher education. The research eventually leads to the conclusion that, under urban-rural segregation, Chinese peasants are compelled to convert their limited economic capital into academic capital, while the reversibility of this capital conversion is hardly objectively guaranteed.